Automated Planter System for Urban Area using IoT Technology - Boon, Hung Yit; Chua, King Lee (Evolution in Electrical and Electronic Engineering, 2021)
Large varieties of smart automatic watering systems have been introduced to support the development of urban agriculture. However, these systems are still not included the action to apply fertilizer which is significant to boost the overall growth of plants. This paper presents the development of an automatic planter system to monitor urban area farming, control the fertilizer mixing process and regulate the watering process. The system is implemented by integrating a typical farming system with a web interface to monitor the farm condition. Electrical conductivity (EC) sensor probes are adopted to monitor EC value and determine an appropriate nutrient solution to be supplied to the plant. To produce a nutrient solution with specific EC, the amount of water and nutrient solution volume are calibrated using the linear-plot method. The system is then tested to produce a nutrient solution with desired EC value. The analysis of test results indicate that the system is able to produce a nutrient solution with a specific EC value with a deviation of 0.2 mS/cm.